A NEW APPROACH TO THE TREATMENT AND PREVENTION OF MORPHOFUNCTIONAL CHANGES IN THE HEART AS A RESULT OF THE EFFECTS OF VARIOUS FACTORS OF THE EXTERNAL AND INTERNAL ENVIRONMENT (LITERATURE REVIEW) - Shukhrat J. Teshayev; Jamshid O. Eshonkulov (Central Asian Journal of Medicine, 2023)
Cardiovascular diseases are the most common causes of morbidity and mortality worldwide. Redox dysregulation and a dyshomeostasis of inflammation arise from, and result in, cellular aberrations and pathological conditions, which lead to cardiovascular diseases. Despite years of intensive research, there is still no safe and effective method for their prevention and treatment. Recently, molecular hydrogen has been investigated in preclinical and clinical studies on various diseases associated with oxidative and inflammatory stress such as radiation-induced heart disease, ischemia-reperfusion injury, myocardial and brain infarction, storage of the heart, heart transplantation, etc. Hydrogen is primarily administered via inhalation, drinking hydrogen-rich water, or injection of hydrogen-rich saline. It favorably modulates signal transduction and gene expression resulting in suppression of proinflammatory cytokines, excess ROS production, and in the activation of the Nrf2 antioxidant transcription factor. Although H2 appears to be an important biological molecule with anti-oxidant, anti-inflammatory, and anti-apoptotic effects, the exact mechanisms of action remain elusive. There is no reported clinical toxicity; however, some data suggests that H2 has a mild hormetic-like effect, which likely mediate some of its benefits. The mechanistic data, coupled with the pre-clinical and clinical studies, suggest that H2 may be useful for ROS/inflammation-induced cardiotoxicity and other conditions.